The Effect of Tourism Policy Implementation To Local Revenue - Biller Pandjaitan (CV. Publikasi Indonesia, 2021)
Tourism contribution has a promising prospect, but it is different from the West Bandung Regency which has 11 tourist attractions but 3 which are managed by the local government, namely ghua pawon, malela waterfall and ciburuy situ. This requires a study to be explored both in terms of Tourism policy implementation as well as implications for local revenue. This study uses qualitative methods of data collection carried out in natural settings, primary data sources, and more data collection techniques in participant observation, in-depth interviews. this study resulted that the original income of the speckle region reached its target because in terms of decision-making it was still dominated by political decisions and unclear ownership of land around the tourist destination, it required coordination and cooperation from the parties to resolve problems in the West Bandung Regency.